New research on the fauna of Heteroptera in Bosnia-Herzegovina (Acta Entomologica Serbica, 2015)
Data on 77 species of Heteroptera collected in 2013 and 2014 from 21 localities in Bosnia-Herzegovina are presented.Eight new species are recorded in Bosnia-Herzegovina for the first time: Gerris costae costae (Herrich-Schaeffer),Myrmecoris gracilis (Sahlberg), Pithanus maerkeli (Herrich-Schaeffer), Aradus obtectus Vásárhelyi, Rhopalus subrufus(Gmelin), Stictopleurus punctatonervosus (Goeze), Leptoglossus occidentalis Heidemann and Trochiscocoris rotundatusHorváth.